Gut microbiota causally affects cholelithiasis: a two-sample Mendelian randomization study - Liu, Xin; Qi, Xingsi; Han, Rongshuang; Mao, Tao; Tian, Zibin (Frontiers in Cellular and Infection Microbiology, 2023)
Background The gut microbiota is closely linked to cholesterol metabolism-related diseases such as obesity and cardiovascular diseases. However, whether gut microbiota plays a causal role in cholelithiasis remains unclear. Aims This study explored the causal relationship between gut microbiota and cholelithiasis. We hypothesize that the gut microbiota influences cholelithiasis development. Methods A two-sample Mendelian randomization method was combined with STRING analysis to test this hypothesis. Summary data on gut microbiota and cholelithiasis were obtained from the MiBioGen (n=13,266) and FinnGen R8 consortia (n=334,367), respectively. Results Clostridium senegalense, Coprococcus3, and Lentisphaerae increased the risk of cholelithiasis and expressed more bile salt hydrolases. In contrast, Holdemania, Lachnospiraceae UCG010, and Ruminococcaceae NK4A214 weakly expressed bile salt hydrolases and were implied to have a protective effect against cholelithiasis by Mendelian randomization analysis. Conclusion Gut microbiota causally influences cholelithiasis and may be related to bile salt hydrolases. This work improves our understanding of cholelithiasis causality to facilitate the development of treatment strategies.